Academic Performance Indicators To Improve Learning Outcomes Of Students In Educational Institutes: Beyond Standardized Tests - Syed Uzma Paiam Bukhari , Muhammad Rafique , Noor Khaliq , Hiralal Hatesh, Nazmeen Umer , Shahid Ahmed , Danish Ahmed Khan , Syeda Vaila Nadeem (Migration Letters, 2024)
Performance indicators provide meaningful information about students’ accomplishments and classroom progress, they are crucial for enhancing student learning. With the use of resources like the Student Academic Performance Indicator, teachers can see trends, patterns, and potential areas where students’ performance could be improved. The study aims to explore the key indicators utilized by teachers to assess students’ learning. The qualitative phenomenological study was used. A sample size was 10 teachers from different schools. A semi-structured questionnaire was used to collect in-depth data from teachers of varied socio-economic backgrounds with different experience levels in the field. The random sampling technique was utilized to assess the population. The data was analyzed through thematic analysis. The major themes for measuring performance indicators that[1] emerged from the data were: teaching pedagogies, Class environment, and exposure given to students. It was explored that a positive class environment, students’ active participation, and extensive exposure to the students are the key factors that help to assess the learning level of students. Recommendations are proposed to teachers based on research findings to enhance the learning process of students and to improve learning outcomes.